Women Crusade for Peace: Claudia Jones and the Cold War Peace Movement. (1st July 2019) - Lynn, Denise
Abstract : After World War II, peace became a central tenet of the Black freedom struggle. But it was also a liability to be associated with peace because the Soviet Union was a major advocate of the peace movement during the Cold War. Claudia Jones, a communist leader and theoretician, was an outspoken, vocal advocate for peace. She argued that war and nuclear weaponry were capitalist tools to limit freedom struggles, contain non-white populations globally, and undermine women's liberties. She argued for women's leadership in the peace movement and advocated a gendered internationalism. Jones, an immigrant herself, believed that American women should advocate for peace beyond national boundaries to secure their own independence, freedom, and equality. This was a particular imperative for Black and colonized women, who, Jones argued, were the most oppressed strata. In order to free all working people and secure a global alliance, women had to become leaders in the peace movement. She saw peace as a necessary prerequisite to undermining capitalist power and reach the full potential of a socialist state. Her advocacy and leadership in the peace movement came at great personal cost. Jones would be arrested, convicted, and deported for her determined political advocacy, all the while her health declined, leading to her premature death. This article argues that Jones's gendered internationalism and peace were central tenets in her vision of a socialist future.